Priložnosti in ovire metapodatkov na slovenskem knjižnem trgu - Jug, Tjaša (Knjižnica, 2019)
Purpose: The Slovenian book market is facing problems, which are, among other, also a consequence of suboptimal processes in metadata management. In our research, we wanted to find which are the most frequent barriers and opportunities regarding meta-data from the catalogers' point of view, as they are one of the most important recipients of publishers' book data and have a good insight into the current situation.Methodology/approach: Participants of our research were six Slovenian catalogers, who are involved in the preparation of CIP records at the National and University Library and the University of Maribor Library. For the purpose of the study, we prepared structured interviews, which were conducted with participants in person or by an e-mail. Results: During their work, Slovenian catalogers have noticed that metadata cause problems especially to smaller and nonprofessional publishers and that issues often originate from their lack of knowledge. The current method of transmitting data is also problematic, since publishers must submit it through various systems to perform all legally required procedures. Despite some concerns, catalogers see many opportunities regarding automatic retrieval of metadata and an introduction of a unified book description system. They believe that although the online service Catsi shows a good potential for process optimization and book description standardization, certain changes should be introduced for this purpose. Research limitations: Besides the small number of participants, the research is also lim-ited due to purposive sampling. The results cannot be generalized, as only the opinions of the participating catalogers are presented while the experiences of other players on the Slovenian book market has not been investigated. Originality/practical implications: The results highlight the current issues of metadata for books and provide the basis for future studies. The findings are important for practitioners who face the identified barriers as well as for system designers who would like to optimize the metadata management process.
Keywords: Catsi; katalogizatorji; metapodatki; Slovenija; založniki